Innovations in Power Systems Reliability - Anders, George; Vaccaro, Alfredo; SpringerLink (Online service) (London : Springer London, 2011)
Electrical grids are, in general, among the most reliable systems in the world. These large interconnected systems, however, are subject to a host of challenges - aging infrastructure, transmission expansion to meet growing demand, distributed resources, and congestion management, among others. Innovations in Power Systems Reliability aims to provide a vision for a comprehensive and systematic approach to meet the challenges of modern power systems. Innovations in Power Systems Reliability is focused on the emerging technologies and methodologies for the enhancement of electrical power systems reliability. It addresses many relevant topics in this area, ranging from methods for balancing resources to various reliability and security aspects. Innovations in Power Systems Reliability not only discusses technological breakthroughs and sets out roadmaps in implementing the technology, but it also informs the reader about current best practice. It is a valuable source of information for academic researchers, as well as those working in industrial research and development.
1. Strategies and Roadmaps to Meet Grid Challenges for Safety and Reliability -- 2. Optimal Maintenance Policies for Power Equipment -- 3. Mathematical and Physical Properties of Reliability Models in View of their Application to Modern Power System Components -- 4. Adequacy Assessment of Wind Integrated Composite Generation and Transmission Systems -- 5. Strategic Lines and Substations in an Electric Power Network -- 6. Transmission Expansion Planning: A Methodology to Include Security Criteria and Uncertainties Using Optimization Techniques -- 7. The Economic Evaluation of System Security Criterion in a Competitive Market Environment -- 8. Probabilistic Transient Stability Assessment and on-Line Bayes Estimation -- 9. Updating System Representation by Trajectory Acquisition in a Dynamic Security Framework -- 10. Reliable Algorithms for Power Flow Analysis in the Presence of Data Uncertainties.
Keywords: Engineering; System safety; Production of electric energy or power; Engineering; Quality Control, Reliability, Safety and Risk; Power Electronics, Electrical Machines and Networks